Fertility treatments and the risk of pediatric obstructive sleep apnea in the offspring—Results from a population‐based cohort study. Issue 10 (1st July 2019) - Imterat, Majdi; Wainstock, Tamar; Sheiner, Eyal; Landau, Daniella; Walfisch, Asnat; Harlev, Avi
Abstract: Objective: While the impact of fertility treatments on the perinatal outcome is well established, the long‐term effects on offspring are yet to be determined. The current study aimed to investigate the risk of long‐term obstructive sleep apnea (OSA) among children born following in vitro fertilization (IVF) and ovulation induction (OI) as compared with spontaneously conceived pregnancies. Study design: A retrospective population‐based cohort study was performed. Exposure was defined as delivery following pregnancies conceived by IVF or OI. Incidence of OSA related hospitalizations of the offspring, up to the age of 18 years, was evaluated. A Kaplan‐Meier survival curve and multivariable Cox regression models were used to assess the association. Results: During the study period, 242 187 singleton deliveries met the inclusion criteria; 1.1% were conceived following IVF (n = 2603), and 0.7% following OI (n = 1721). Offspring hospitalization rates, involving OSA (n = 1607), were higher among children conceived following IVF and OI pregnancies as compared with the rate in children conceived spontaneously (1.4% vs 1.2% vs 0.7%, respectively; P  < .001). The Kaplan‐Meier survival curve demonstrated a significantly higher cumulative incidence of OSA related hospitalizations following IVF and OI (log‐rank P  < .001). Using multiple Cox regression models, controlled for gestational age, maternal age, maternal smoking, maternal obesity, birthweight, offspring gender and obesity, IVF as well as OI exhibited a significant and independent association with pediatric OSA in all models with adjusted hazard ratios of 2.25, (95% confidence interval [CI] = 1.6‐3.1) and 1.63 (95% CI = 1.1‐2.5), respectively. Conclusion: Both IVF and OI treatments appear to be independently associated with OSA in the offspring.